2017
DOI: 10.20853/31-4-878
|View full text |Cite
|
Sign up to set email alerts
|

'So I decided not to invade straight black men's space': exploring heteronormative spaces on campus

Abstract: Challenging heteronormative spaces has been identified as one of the key difficulties facing the issue of destabilisation of deeply entrenched gendered and sexual practices and spaces within institutional contexts. In a university context, that includes a hegemonic masculine student residence culture; this may be even more challenging and disrupting to how one mediates social and academic space. Challenging includes awareness of how one may be able to challenge, as well as moments when one is not able to chall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…Male residents seem to be hot spots for homophobia in some South African universities (Graziano 2004). Evidently, 12 years later this remains unchanged and in their article Kiguwa and Langa (2017), describe how research participants negotiate this environment whilst making attempts to challenge it. Three of these articles reflect on lesbian identities and experiences (Prado-Castro and Graham 2017; Naidu and Mutambara 2017;…”
Section: Introductionmentioning
confidence: 99%
“…Male residents seem to be hot spots for homophobia in some South African universities (Graziano 2004). Evidently, 12 years later this remains unchanged and in their article Kiguwa and Langa (2017), describe how research participants negotiate this environment whilst making attempts to challenge it. Three of these articles reflect on lesbian identities and experiences (Prado-Castro and Graham 2017; Naidu and Mutambara 2017;…”
Section: Introductionmentioning
confidence: 99%
“…The article examines the systemic and structural manner in which the university space can be a site of coloniality that not only marginalises but also exploits female and queer people. It departs from the observation that, while significant research has been carried out on gender (Barnes, 2007;Bennet, 2002;Gaidzanwa, 2000;Mama, 2003;Ndhlovu & Masuku, 2004;Okeke, 2003;Otunga & Ojwang, 2003;Pereira, 2007;Zindi, 1994) and sexuality (Francis & Msibi, 2011;Kiguwa & Langa, 2017;Msibi, 2009Msibi, , 2013 in African universities, there is a paucity of reflective literature on heterosexual men's experiences of gender and sexuality in these spaces-in what Msibi (2013, p. 1) called the "the silencing of queer issues in higher education." While they dealt with coloniality as a system implicit in epistemic injustices, scholars (Almeida & Kumalo, 2018;Ndlovu-Gatsheni, 2013;Mpofu, 2013) barely accounted for how it informs the gender and sexuality-based oppressions that take place in the university as a result of the hierarchisation that coloniality enforces.…”
Section: Introductionmentioning
confidence: 92%
“…Msibi (2009) posited that apart from being a gendered environment, the university in Africa is also hostile towards non-heterosexual identities. Recent research conducted in South Africa has shown that university residences remain one of the most homophobic spaces, deeply entrenched in heteronormative cultures that exclude queer students (Jagessar & Msibi, 2015;Kiguwa & Langa, 2017). Bennet (2002) suggested that the higher education environment in Africa is a site for the performance of heterosexuality as a major route into resources, stability, identity, and citizenship.…”
Section: Theoretical Considerations: Why Gender and Sexuality Mattermentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, the studies suggest that campus communities (including student residences) are not places where LGBTI students feel fully safe or comfortable: 'Most of the research findings … [in this issue] indicate that the institutions of higher education in SADC are still heteronormative and LGBTI staff and students are marginalized, prejudiced and discriminated against' (Nduna, Mthombeni, Mavhandu-Mudzusi, & Mogotsi, 2017, p. 1; see also Munyuki & Vincent, 2017). LGBTI students at an unnamed rural university reported regular threats of violence and theft (Mavhandu-Mudzusi & Sandy, 2017); black gay men living in all-male residences at Wits reported institutionalised homophobia in student residence house committees (Kiguwa & Langa, 2017). Lesch, Brits, and Naidu (2017) show how same-sex couples have to monitor their behaviour on campus, knowing precisely which parts of campus are gay-friendly and which are not, and are nervous to publicly display affection for fear of backlash or of causing offence.…”
Section: Experiences Of Institutional Discrimination Other Than Racismmentioning
confidence: 99%